A validation study of the Ursodeoxycholic Acid Response Score in Japanese patients with primary biliary cholangitis. (30th May 2020) - Yagi, Minami; Matsumoto, Kosuke; Komori, Atsumasa; Abe, Masanori; Hashimoto, Naoaki; Inao, Mie; Namisaki, Tadashi; Kawata, Kazuhito; Ninomiya, Masashi; Fujii, Hideki; Takahashi, Atsushi; Kang, Jong‐Hon; et al.
Abstract: Background/Purpose: Although ursodeoxycholic acid (UDCA) is a first‐line treatment for primary biliary cholangitis (PBC), 20%‐30% of patients with PBC exhibit an incomplete response to UDCA. Recently, the UDCA Response Score was proposed for predicting response to UDCA using pretreatment parameters in patients with PBC. We aimed to validate the UDCA Response Score in Japanese patients with PBC. Methods: Registry data of Japanese patients (n = 873) were collected. Patients with data on all clinical parameters required for calculating the UDCA Response Score were selected. The endpoint was UDCA response, defined as alkaline phosphatase <1.67 times the upper limit of the normal value after 12 months of UDCA treatment. Results: All parameters were available in 804 patients (male/female = 120/684, age 58.9 [interquartile range 51.1‐66.9] years). Bezafibrate was commenced within 12 months of UDCA in 78 patients (9.7%) because of the lack of an early response. We found that the endpoint was not reached in these 78 patients, and the area under the receiver operating characteristic curve (AUROC) of the score was 0.74 (95% confidence interval [CI] 0.70‐0.79). The AUROC was 0.77 (95% CI 0.70‐0.83) in patients undergoing UDCA monotherapy (n = 726). Finally, the AUROC of the modified UDCA Response Score using only data from the treatment start date was 0.80 (95% CI 0.70‐0.90) in patients receiving a combination therapy of UDCA and bezafibrate (n = 160). Conclusion: The validity of the UDCA Response Score was acceptable in Japanese patients; this score will be informative in patients treated with a combination therapy of UDCA and bezafibrate.